ENGLISH PROFICIENCY AND METACOGNITIVE STRATEGIES USED BY ENGLISH DEPARTMENT STUDENTS AT IAIN ANTASARI BANJARMASIN - Saadillah, Saadillah; Nor, Hidayah (English Department of Faculty of Tarbiyah and Teachers Training, 2015)
Metacognitive strategies play important roles to develop skills in the process of learning a target language. This studyÂ investigated the metacognitive strategies and the frequency used by English Department students at IAIN Antasari Banjarmasin and determined how those metacognitive strategies were influenced by the learnersâ proficiency. 105 respondents who participated in this study were the first semester students in English Department. The subjects learned English as a foreign language and were at beginning level. The strategy use was assessed through a modified Indonesian translation version of the Strategy Inventory of Language Learning (Oxford, 1990), and the proficiency was determined by the TOEFL Test. The data were distributed and analyzed using descriptive statistics. Â It can be concluded that the use of metacognitive strategies among the three categories (low, middle, and high) is quite different which is the most frequent metacognitive strategies used by studentsâ middle category group with the MeanÂ = 4.031, followed by studentsâ high category group with the MeanÂ = 3.765, and the least metacognitive strategies used by studentsâ low category group MeanÂ = 3.091. The types of meta-cognitive strategies thatÂ used by the students, including paying attention when someone is speaking English (88%), trying to find out how to be a better learner of English (85%), having clear goals for improving English skills (82%), noticing the mistakes (82%), thinking about their progress in learning EnglishÂ (67%)Â , tryingÂ to find as many ways as they can use their EnglishÂ (59 %), planning their schedule so they will have enough time to study English (57 %),Â looking for people whom they can talk to in EnglishÂ (52 %), and looking for opportunities to read as much as possible in English (35 %).